Comparison of BRCAx tumors with BRCA1-, BRCA2-carriers and non-familial breast cancer. - BRACKEN, ADRIAN (My University, 2015)
Aims Women with inherited pathogenic mutations in the BRCA1 or BRCA2 genes have up to an 85% risk of developing breast cancer in their lifetime. However, only about 20% of familial breast cancer is attributed to mutations in BRCA1 and BRCA2, while a further 5–10% are attributed to mutations in other rare susceptibility genes such as TP53, STK11, PTEN, ATM and CHEK2. Despite extensive efforts to explain the missing heritability of this disease, the majority of familial clustering in breast cancer remains largely unexplained. We aim to analyze the pathology of familial cases of which no pathogenic mutation is yet identified. Methods We compared the pathological phenotype of BRCA1/BRCA2 negative familial breast cancer (BRCAx) to BRCA1-positive, BRCA2-positive and sporadic cases without a family history. Age-adjusted analysis is summarized in odd's ratios and confidence intervals for tumor type, grade, lymph node, ER and HER2 status. Results We found non-familial cases to be more likely to be ER positive (P = 0.041) as compared with BRCAx tumors. More cases of lobular carcinoma were found with BRCAx as compared to BRCA1 tumors (P = 0.05). After multivariate logistic regression analysis, BRCAx tumors are more likely ER positive (P = 0.001) and HER2 positive (P = 0.047) in comparison to BRCA1. Conversely, BRCAx cases are less likely to be ER positive (P = 0.02) but more likely to be HER2 positive (P = 0.021) as compared with BRCA2 tumors. Conclusion Our findings suggest that BRCA1, BRCA2 and BRCAx tumors differ in phenotype from non-familial and familial BRCA1-positive and BRCA2-positive tumors. Further studies will need to be performed in this important population in order to develop strategies for early detection and prevention.
PUBLISHED
Keywords: Breast cancer; BRCA1 gene; BRCA2 gene; Selective estrogen receptor modulators; Genetics; Chemoprevention; Breast cancer; BRCA1 gene; BRCA2 gene; Selective estrogen receptor modulators; Genetics; Chemoprevention; Cancer; Genes & Society